Biodiversity Web Resources - Creech, John (Issues in Science and Technology Librarianship, 2012)
The article reviews several science and technology resources Web sites including the Tree of Life Project (ToL) located at http://tolweb.org/tree/, the Encyclopedia of Life (EOL): Explore Biodiversity Resources located at http://eol.org/info/23: and the Ocean Portal: Smithsonian Institution located at http://ocean.si.edu/.